2022
DOI: 10.3389/fnins.2022.779964
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Listening to Varying Synchrony Between Beats in Samba Percussion and Relations to Feeling the Groove

Abstract: Listening to samba percussion often elicits feelings of pleasure and the desire to move with the beat—an experience sometimes referred to as “feeling the groove”- as well as social connectedness. Here we investigated the effects of performance timing in a Brazilian samba percussion ensemble on listeners’ experienced pleasantness and the desire to move/dance in a behavioral experiment, as well as on neural processing as assessed via functional magnetic resonance imaging (fMRI). Participants listened to differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 116 publications
0
18
1
Order By: Relevance
“…This listener experience might for example be triggered by a regular beat in the music. The hypothesis is supported by empirical results that show a positive relationship between the urge to move and the salience of the regular beat (Engel et al, 2022, Madison et al, 2011Percival, 2021), and by theoretical studies on the synchronization of music and movement (Merker, 2014;Oliver, 2016).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…This listener experience might for example be triggered by a regular beat in the music. The hypothesis is supported by empirical results that show a positive relationship between the urge to move and the salience of the regular beat (Engel et al, 2022, Madison et al, 2011Percival, 2021), and by theoretical studies on the synchronization of music and movement (Merker, 2014;Oliver, 2016).…”
Section: Introductionmentioning
confidence: 87%
“…-Microtiming was discussed as potentially relevant to the urge to move, but empirical results were inconsistent (Brøvig-Hanssen et al, 2021, Câmara et al, 2020a, 2020b, Cameron et al, 2019Datseris et al, 2019;Davies et al, 2013;Engel et al, 2022;Frühauf et al, 2013;Ganis et al, 2021;Hofmann et al, 2017;Keil, 1987;Kilchenmann & Senn 2015;Matsushita & Nomura, 2016;Nelias et al, 2022;Senn et al, 2016;Skaansar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The research reviewed earlier has revealed that observers are sensitive to fine-grained temporal contingencies between both sounds and movements produced by musical coperformers, although perceptual judgments of the level of coordination within musical ensembles can be influenced or biased by a variety of factors, from elements of the musical structure and ensemble roles to the modality of stimulus presentation and the expertise of the listener. As subjective judgments of the synchronicity of a performance can also influence audience reactions to music, from the appraisal of performance quality to emotional and motor responses (Engel, Hoefle, Monteiro, Bramati, et al, 2014; Engel, Hoefle, Monteiro, Moll, & Keller, 2014; Labbé & Grandjean, 2014; Trost, Labbé, & Grandjean, 2017), understanding the factors that potentially underlie these judgments has key implications for research on both nonverbal interpersonal communication and music performance evaluation.…”
Section: The Present Researchmentioning
confidence: 99%
“…It is seen that music, when used as an intervention, affects health [ 4 , 5 ] through different processes, which are yet to be well understood. Mechanisms put forth include the impact on the nervous system, the limbic system, [ 6 ] the autonomic nervous system [ 7 ], as well as synchronization of the body’s natural rhythms (for example, heart rate or respiratory rate) with the rhythm of the music [ 1 , 2 , 8 ]. Music is a safe, inexpensive, easily administered intervention that can be used for anxiety reduction and has proven to be beneficial in various diseases that include cardiovascular, neurological and oncological diseases, as reviewed in [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%